Key opportunities for the future of roads to contribute to Australia's climate change response - Hargroves, Charlie; Beattie, C.; Wilson, L.; Newman, Peter; Matan, Annie; Desha, C. (2014)
Road agencies face growing pressure to respond to a range of issues associated with climate change and the reliance on fossil fuels. A key part of this response will be to reduce the dependency on fossil fuel based energy (and the associated greenhouse gas emissions) of transport, both vehicles and infrastructure. This paper presents findings of investigations into three key areas of innovative technologies and processes, namely the inclusion of onsite renewable energy generation technologies as part of road and transport infrastructure, the potential for automated motorways to reduce traffic fuel consumption (referred to as ‘Smart Roads’), and the reduction of energy demand from route and signal lighting. The paper then concludes with the recommendation for the engineering profession to embrace sustainability performance assessment and rating tools as the basis for enhancing and communicating the contribution to Australia’s response to climate change. Such tools provide a rigorous structure that can standardise approaches to key issues across entire sectors and provide clarity on the evidence required to demonstrate leading performance. The paper has been developed with funding and support provided by Australia’s Sustainable Built Environment National Research Centre (SBEnrc), working with partners including Main Roads Western Australia, NSW Roads and Maritime Services, Queensland Department of Transport and Main Roads, John Holland Group, the Infrastructure Sustainability Council of Australia, Roads Australia, and the CRC for Low Carbon Living.